2019
DOI: 10.1186/s11671-019-2942-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Filament Overgrowth in Conductive Bridge Random Access Memory by Ta2O5/TaOx Bi-Layer Structure

Abstract: Bi-layer structure has been widely adopted to improve the reliability of the conductive bridge random access memory (CBRAM). In this work, we proposed a convenient and economical solution to achieve a Ta 2 O 5 /TaO x bi-layer structure by using a low-temperature annealing process. The addition of a TaO x layer acted as an external resistance suppressing the overflow current during set programming, thus achieving the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
(17 reference statements)
0
15
0
1
Order By: Relevance
“…It is reported that Cu ions drift in the TaOx layer is low under electric field; 32 hence the device requires high Vforming (Fig. 1(a)).…”
Section: Based On Above Investigation We Propose the Conduction Mechanisms For Device A Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that Cu ions drift in the TaOx layer is low under electric field; 32 hence the device requires high Vforming (Fig. 1(a)).…”
Section: Based On Above Investigation We Propose the Conduction Mechanisms For Device A Andmentioning
confidence: 99%
“…In the case of Device A, the potentiation exhibits abrupt conductance change and require a higher amplitude than that of Device B; this is because of the low mobility of Cu ions in the TaOx material and, thus, a higher electric field is required to ionize the ions. 32,36 However, once the device is potentiated (complete filament formation), the depression shows a gradual conductance change. This is because it is easier to re-ionize and pulse the Cu atoms back to the top region since the tip of the filament is connected directly or close to the electrode.…”
Section: (B)(i))mentioning
confidence: 99%
“…This implies that the overgrowth of the CFs was promoted by the current overshoot phenomenon. [ 30,31 ] Note that in conventional ECM systems, the stored charges in the device cause the current to exceed the CC value. In contrast, the current level in the LRS of Device 2 saturated at a certain value (≈8 × 10 −6 A) below the CC (Figure 2b), indicating that the CF growth was controlled to avoid the overshoot phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, multilayer metal oxides are used as the switching materials in the CBRAMs to enhance the switching characteristics of the devices. Yu et al used a tantalum oxide homogeneous bilayer switching medium with a different stoichiometry for each layer [ 43 ]. The CBRAM device with a Ta 2 O 5 /TaO x bilayer stack presents highly reliable and uniform bipolar switching ( Figure 4 c).…”
Section: Electrode and Switching Materialsmentioning
confidence: 99%